Utilization of Position Check Techniques in the Investigation of the Crime of Theft with Aggravated Circumstances by the Surabaya Police Criminal Investigation Unit - James Tirtamas (Advances in Police Science Research Journal, 2021)
Technology nowadays holds an important role in every aspect of life, namely economy, culture, defense, and security. All stakeholders should be able to take positive benefits of technology, albeit it has negative impacts as well. This research is conducted because of the difficulty to reveal the larceny criminal acts with aggravation in the condition where there is lack of witnesses, evidence, guides, and other information about the larceny suspect with aggravation. In line with the background of problem, the author writes the thesis in titled “The Utilization of Location Tracking for Larceny Criminal Acts Investigation with Aggravation by Satreskrim Polrestabes Surabaya”. The purposes of this research are to know the description of larceny cases with aggravation, to obtain data about the procedure of location tracking method, and to identify the factors that influence the usage of location tracking method. Moreover, analytical theory and management theory are both being used for this research. Furthermore, in this research the author adopts investigation concept and criminal acts concept with aggravation which regulated in the article 363 KUHP. The result of the research based on literature review and interview shows that the location tracking method is very useful to support the criminal acts investigation, especially larceny with aggravation that being handled by Satreskrim Polrestabes Surabaya. The conclusion of this research is that the stages of the location tracking method, which has been done by Satreskrim Polrestabes Surabaya, has effectively helped the object to reveal the larceny criminal acts including the factors involved.